PROBLEMS OF ENSURING INFORMATION SECURITY IN THE TRAINING OF FUTURE OFFICER PERSONNEL AND THEIR SOLUTION - Bekpulatov , Habibulla Bakhridinovich (Educational Research in Universal Sciences, 2023)
In this article, the modern methods of training military teaching personnel, the potential for developing their innovative abilities, the importance of the innovative approach in this direction, the possibilities of achieving effective results in the training process, as well as the levels and scope of the acmeological approach in pedagogical skills are covered.